2008
DOI: 10.2131/jts.33.187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetyltransferase 2 (NAT2), CYP2E1 and Glutathione-S-transferase (GST) genotypes on the serum concentrations of isoniazid and metabolites in tuberculosis patients

Abstract: -For the purpose of a side-effect monitoring of isoniazid (INH), we investigated the relationship between the genotypes of drug-metabolizing enzymes involved in INH metabolism and the serum concentrations of INH and its metabolites in 129 tuberculosis patients hospitalizing in the National Hospital Organization Chiba-East Hospital. Genotype distributions of N-acetyltransferase 2 (NAT2), CYP2E1*5B, CYP2E1*6, Glutathione-S-transferase (GST) M1 and GST T1 were similar to those already reported in Japanese populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 17 publications
(15 reference statements)
2
37
1
1
Order By: Relevance
“…PZA increases the hepatotoxicity of INH [34], and nontoxic concentrations of INH and hydrazine increase in-vitro PZA hepatotoxicity [35]. Several surveys reported that genetic alterations in the enzymes involved in the metabolic pathways of INH were associated with hepatotoxicity [36][37][38][39]. We investigated the pharmacogenetics of INH, and our results support this hypothesis.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…PZA increases the hepatotoxicity of INH [34], and nontoxic concentrations of INH and hydrazine increase in-vitro PZA hepatotoxicity [35]. Several surveys reported that genetic alterations in the enzymes involved in the metabolic pathways of INH were associated with hepatotoxicity [36][37][38][39]. We investigated the pharmacogenetics of INH, and our results support this hypothesis.…”
Section: Discussionsupporting
confidence: 70%
“…The median age of the total study population was 29 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) years and 128 (46.9%) patients were women. The median BMI was 20.8 (18.7-22.4) kg/m 2 and 5.7% were severely underweight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5, is theoretically possible that GST isoforms, which are genetically determined to a great extent, may also influence INH metabolism. In this way, a study found that well known GSTM1 null genotype influenced the serum concentration of Hz in the NAT2 slow acetylators independently of their CYP2E1 phenotype (Fukino et al 2008). Thus, more efforts are necessary to uncover the important question: interactions between NAT2 and CYP2E1 phenotypes, in addition to the GSTs, may have potential risks for isoniazid-induced hepatotoxicity?…”
Section: Clinical Pharmacogenetics and Potential Applicationsmentioning
confidence: 99%
“…Several studies had been studied about the relationship between acetylator status and risk of hepatotoxic; all of which showed a significant correlation. 3,5,6,9,10,11,12 Otherwise, the proportions of slow acetylator were varies in several studies. Thus indicated the different risk for hepatotoxic effect in different population.…”
Section: Introductionsmentioning
confidence: 99%